Neuropsychological Assessment of Hippocampal Integrity. Issue 2 (4th March 2017) - Saury, Jean-Michel; Emanuelson, Ingrid
ABSTRACT: Finding methods to describe subcortical processes assisting cognition is an important concern for clinical neuropsychological practice. In this study, we reviewed the literature concerning the relationship between a neuropsychological instrument and the underlying neural substructure. We examined evidence indicating that one of the oldest neuropsychological tests still in use, the Rey Auditory Verbal Learning Test (RAVLT), includes reliable indicators of hippocampal integrity. We reviewed studies investigating the neural structures underlying seven tasks generated by the RAVLT, from the perspective of whether the performance of these tasks is dependent on the hippocampus. We found support for our hypothesis in five cases: learning capacity, proactive interference, immediate recall, delayed recall, and delayed recognition. No support for our hypothesis was found with regard to short-term memory and retroactive interference. The RAVLT appears to be a reliable tool for assessing the integrity of the hippocampus and for the early detection of dysfunction. There is a need for such assessments, due to the crucial role of the hippocampus in cognition, for instance, in terms of predicting future outcomes.